Breakthrough in agricultural policy, or another policy failure? - Ulrich Koester; Heinrich Terwitte (Intereconomics, 1988)
Before the European summit in February 1988, EC agricultural policy was being criticized by almost all those affected. Farmers complained about low incomes and the lack of prospects, consumers and taxpayers about the high cost of agricultural support, politicians about spending commitments that could no longer be financed, agricultural economists about the waste of economic resources and trading partners about disruption of the world market. Have the decisions taken at the European summit set the Community on a fundamentally new course?
Keywords: 330; European Community